O jogo entre interpretação e performance em "Meu tio o Iauaretê, de Guimarães Rosa - Tait, Thais Calvi (2007)
This research s goal is to investigate the reading as an interpretation task and a performance act, based on the reading and the reader teories of Iser, and of the Zumthor s studies about the reader, the body and the voice. The reflection about the reader s narrative category will have by analysis corpus the short story Meu tio o Iauaretê , by Guimarães Rosa. A narrative that takes the word until the limit of the non-word, by way of grumbles, onomatopoeias and other sound groups, that are vocal presences although non-linguistics. Such disarticulation creates a jaguar-language , making the narrative a metamorphosis space, no matter if it is the narrator and the interlocutor, in the history plan, no matter if it is implicit the author and the reader on the speech s plan. Then, three roles possibilities are opened for the empiric reader on his interaction with the text: the interlocutor ones or reader s fiction , inscribed in his own history; the reader ones that is implicit in his action of fulfilling the empities of the text and the perfomer-reader ones in the act of multisensorial immersion being face to face with this vocalized literary text